Pola Asuh Keluarga Single Parent dalam Meningkatkan Prestasi Anak Pada Usia 7-12 Tahun di Dusun Jemparing Desa Pakel Kecamatan Bareng Kabupaten Jombang - Zamroji, Muhammad; ‘Aini, Robi’ul Afif Nurul; Aslamiyah, Tsuwaibatul (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2022)
Single parent family in increasing children’s achievement in the village of Jemparing in Pakel village, subdistrict bareng together with various ways, namely by giving raise and encouging the child to be enthusiastic in learning and also need guidance, facilities and motivation so that the child is more happy or active in learning. Mentoring when children learn provide the right to rest, rights in health services and child protection rights. The role of single parent families in increasing children’s academic and non academic achievement is also a variety of ways to do that is by providing guidance with advice, praise, motivation, and gifts if the child gets achievements, accompanying when they are studying, and giving facilities which are needed by the children.